Enhancing children's math motivation with a joint intervention on mindset and gender stereotypes. (June 2021) - Lee, Jeesoo; Lee, Hyun Ji; Song, Juyeon; Bong, Mimi
Abstract: We tested the effectiveness of the intervention program designed to enhance children's math motivation by simultaneously strengthening their growth mindsets and weakening their gender stereotypes. Both the intervention and control programs consisted of six bi-weekly 40-min sessions that were evenly distributed over three months and administered during regular school hours. Repeated measures analyses of variance with group (between-subject factor: intervention vs. control) and time (within-subject factor: pretest vs. posttest) revealed significant Group × Time interactions for all outcomes but test anxiety. Growth mindset, perceived competence, persistence, and achievement of the intervention group increased, while those of the control group decreased. Gender stereotypic beliefs exhibited the opposite pattern. Also, growth mindset and gender stereotypes correlated negatively only for the intervention group. Path analysis demonstrated that the growth mindset of students after the intervention predicted their math persistence and achievement directly and indirectly via their perceived competence in math. Highlights: A math intervention improved fourth-graders' growth mindset and gender-fair belief. The intervention also improved students' math competence and achievement. Simultaneously addressing mindset and gender stereotypes proved effective. Growth mindset enhancement was more helpful for children than anti-stereotyping. The intervention more effectively reduced math test anxiety for boys than girls.